1995
DOI: 10.1029/95ja02858
|View full text |Cite
|
Sign up to set email alerts
|

Gravity waves near 300 km over the polar caps

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
74
1
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 7 publications
(4 reference statements)
12
74
1
3
Order By: Relevance
“…It is easy to see that the wave propagates in reverse flight direction (leftwards in the plot). Almost all observed polar AGWs were propagating towards the dayside (Johnson et al, 1995;Fedorenko and Kryuchkov, 2011a). Note that the systematic phase shift between the density variation of different gases in Fig.…”
Section: Observational Signaturesmentioning
confidence: 88%
See 2 more Smart Citations
“…It is easy to see that the wave propagates in reverse flight direction (leftwards in the plot). Almost all observed polar AGWs were propagating towards the dayside (Johnson et al, 1995;Fedorenko and Kryuchkov, 2011a). Note that the systematic phase shift between the density variation of different gases in Fig.…”
Section: Observational Signaturesmentioning
confidence: 88%
“…In the day sector the region of increased wave activity is bounded by the auroral oval, but in the night sector it can span down to lower geomagnetic latitudes. The dominant horizontal wavelength in the polar thermosphere is 500-600 km (Fedorenko and Kryuchkov, 2011a;Johnson et al, 1995). In the following subsections we briefly summarize the main features of polar AGWs as deduced primarily from DE2 measurements.…”
Section: Properties Of Polar Agwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from Dynamics Explorer 2 satellite, Johnson et al [1995] reported quasisinusoidal patterns of vertical velocity of both ions and neutrals over the polar caps. Shiokawa et al [2003] discussed a simultaneous ground-satellite observation of a nighttime MSTID event using DMSP F15 satellite data and airglow images from ground-based observation.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al, 1988;Fukao et al, 1993), satellite (e.g. Johnson et al, 1995) and tomographic techniques (e.g. Pryse et al, 1995), and have cast light on the validity of theoretical and numerical models (e.g.…”
Section: Introductionmentioning
confidence: 99%